Peptide Conjugation Enhances the Cellular Co-localization, but not Endosomal Escape, of Modular Poly(Acrylamide-co-Methacrylic Acid) Nanogels - Clegg, John R. (J Control Release, 2020)
Nanoparticles must recognize, adhere to, and/or traverse multiple barriers in sequence to achieve cytosolic drug delivery. New nanoparticles often exhibit a unique ability to cross a single barrier (i.e. the vasculature, cell membrane, or endosomal compartment), but fail to deliver an adequate dose to intracellular sites of action because they cannot traverse other biological barriers for which they were not optimized. Here, we developed poly(acrylamide-co-methacrylic acid) nanogels that were modified in a modular manner with bioactive peptides. This nanogel does not recognize target cells or disrupt endosomal vesicles in its unmodified state, but can incorporate peptides with molecular recognition or environmentally responsive properties. Nanogels were modified with up to 15 wt% peptide without significantly altering their size, surface charge, or stability in aqueous buffer. Nanogels modified with a colon cancer-targeting oligopeptide exhibited up to a 324% enhancement in co-localization with SW-48 colon cancer cells in vitro, while influencing nanogel uptake by fibroblasts and macrophages to a lesser extent. Nanogels modified with an endosome disrupting peptide failed to retain its native endosomolytic activity, when coupled either individually or in combination with the targeting peptide. Our results offer a proof-of-concept for modifying synthetic nanogels with a combination of peptides that address barriers to cytosolic delivery individually and in tandem. Our data further motivate the need to identify endosome disrupting moieties which retain their activity within poly(acidic) networks.